Cases of tetrasomy 9p and trisomy 9p in prenatal diagnosis—Analysis of noninvasive and invasive test results - Moczulska, Hanna; Pietrusinski, Michal; Zezawska, Karolina; Serafin, Marcin; Skoczylas, Beata; Jachymski, Tomasz; Wojda, Katarzyna; Sieroszewski, Piotr; Borowiec, Maciej (Frontiers in Genetics, 2022)
Tetrasomy 9p is a rare chromosomal aberration described in approximately 60 patients. Due to the milder phenotype, trisomy 9p is seen more frequently. Most of the cases were diagnosed in the postnatal period. The study aims to analyze the prenatal phenotype of tetrasomy 9p and trisomy 9p in terms of ultrasound and screening tests. We analyzed 1573 prenatal tests to find all cases with trisomy 9p and tetrasomy 9p. We observed four cases with the 9p amplification diagnosed in the prenatal period: two cases with tetrasomy 9p and two cases with trisomy 9p. The first case with tetrasomy 9p presented nasal bone hypoplasia, cleft lip, abnormal posterior fossa, and a congenital heart defect. The second case with tetrasomy 9p demonstrated corpus callosum agenesis, ventriculomegaly, abnormal posterior fossa, bilateral cleft lip and palate, nasal bone hypoplasia, retrognathia, pleural effusion, pyelectasis, and clenched hands. Case with trisomy 9p and 22q11 duplication presented ventriculomegaly, nasal bone hypoplasia, aberrant right subclavian artery, mild pulmonary stenosis, tricuspid regurgitation, long bone shortening, abnormal posterior fossa, and polyhydramnios. The second case with trisomy 9p manifested ventriculomegaly, fetal growth restriction, and club foot. An increased risk of trisomy 21 was found in two out of four cases with the 9p amplification. Trisomy 9p and tetrasomy 9p are characterized by variable phenotypes in the prenatal period. Nasal bone hypoplasia and ventriculomegaly are common features of the 9p amplification. The clinical picture of the 9p amplification in the first trimester might mimic trisomy 21.